Вихідний матеріал для селекції зернобобових культур з покращеними технологічними показниками насіння - Кобизєва, Л.Н. (Фактори експериментальної еволюції організмів, 2013)
Aims. The article introduces results of many years studying (1994–2009 yy.) of collection samples of pea, bean, chick-pea and lentil of the National centre of studying genetic plant resources of Ukraine by technological indices of seeds – time of boiling and overcooking coefficient. Methods. The determination of technological characteristics of seeds of leguminous plants (overcooking and taste qualities) have been determined by commonly accepted methodology (1992 y.). Results. It has been determined that as for the time of boiling, all the studied crops are characterized by considerable range, that confirms the wide range of input material for working-off in the selective plan of this characteristic. Depending on crops ,the overcooking coefficient was changing from 1,6 till 5,7; depending on weather conditions it was not stable (V from 6 % till 18,47 %). The samples of pea have been defined as the highest overcooking coefficient. Conclusions. The collection samples of bean (V=18,47 %) and pea (V=18,26 %) are characterized by the biggest changeability of the overcooking coefficient. Most of samples has had satisfactory and good time of boiling: pea (35,48 %, 39,67 %), bean (53,8 %, 33,7 %), and chick-pea (49,4 %, 42,1 %) accordingly, in lentil the studied samples have had good (53,5 %) and excellent (37,5 %) time of boiling.